Faktor- Faktor yang Berhubungan dengan Pemanfaatan Pelayanan Antenatal di Wilayah Kerja Puskesmas Air Tawar Kota Padang - Desi Andriani; Husna Yetti; Roza Sriyanti (Universitas Batanghari Jambi, 2019)
Antenatal care or antenatal care is a planned program that is observation, education and medical treatment for pregnant women, to obtain a safe and satisfying pregnancy and childbirth process. The indicator used to assess the access of pregnant women to antenatal care is K1 direction (first visit) is the contact of pregnant women to health workers and K4 (perspective visit) is 4 or more times contact with health workers. From the data of the Padang City Health Office, it was found that the Air Tawar Puskesmas with this low level was caused by various factors. The purpose of this study was to determine factors related to the use of antenatal services. This type of research is a quantitative study with cross sectional study design with 110 respondents of third trimester pregnant women with purposive sampling technique. Data analysis was performed univariate, bivariate with Chi squre test. From the research results obtained from the five factors studied, it was found that the factors related to the use of antenatal services in freshwater health centers were access or distance with pvalue 0.009 = OR 21.676), service availability factors with a p value of 0.001 = OR 9.293, the role factor midwives with a p value of 0.001 = OR 12.302, while the family income factor, disease complaints obtained results have nothing to do with the use of antenatal services. The author's suggestion is that there is a need for good coordination with the Independent Practice Midwife (BPM), revitalize puskesmas to more strategic places and improve better facilities, improve accessibility that can be minimized, strive to reach pregnant women, especially for accessibility that is less affordable.